Machine Learning Approaches to Identifying Changes in Eruptive State Using Multi‐Parameter Datasets From the 2006 Eruption of Augustine Volcano, Alaska. Issue 12 (14th December 2021) - Manley, Grace F.; Mather, Tamsin A.; Pyle, David M.; Clifton, David A.; Rodgers, Mel; Thompson, Glenn; Roman, Diana C.
Abstract: Understanding the timing of critical changes in volcanic systems, such as the beginning and end of eruptive behavior, is a key goal of volcanic monitoring. Traditional approaches to forecasting these changes have used models motivated by the underlying physics of eruption onset, which assume that geophysical precursors will consistently display similar patterns prior to transition in volcanic state. We present a machine learning classification approach for detecting significant changes in patterns of volcanic activity, potentially signaling transitions during the onset or end of volcanic activity, which does not require a model of the physical processes underlying critical changes. We apply novelty detection, where models are trained only on data prior to eruption, to the precursory unrest at Augustine Volcano, Alaska in 2005. This approach looks promising for geophysically monitored volcanic systems which have been in repose for some time, as no eruptive data is required for model training. We compare novelty detection results with multi‐class classification, where models are trained on examples of both non‐eruptive and eruptive data. We contextualize the results of these classification models using constraints from petrological, satellite and visual observations from the 2006 eruption of Augustine Volcano. The transition from non‐eruptive to eruptive behavior we identify in mid‐November 2005 is in agreement with previous estimates of the initiation of dike intrusion prior to the 2006 eruption. We find that models which include multiple types of data (seismic, deformation, and gas emissions) can better distinguish between non‐eruptive and eruptive data than models formulated on single data types. Plain Language Summary: Identifying the onset of volcanic activity is a central goal of volcanology. We apply machine learning approaches to seismic, gas and geodetic data in order to classify eruptive and non‐eruptive activity. We consider models trained on only pre‐eruptive data, and models trained on both non‐eruptive and eruptive data. Our models begin to identify eruptive behavior in mid‐November 2005, which coincides with previous estimates of the beginning of transport of magma to the surface. We compare the models constructed using all data types to those made with each data type individually. We find that models which include multiple types of data are better at identifying non‐eruptive and eruptive activity. Key Points: Application of one‐class and multi‐class machine learning classification to seismic, gas and geodetic time series from the 2006 eruption of Augustine Volcano, Alaska We identify a transition from non‐eruptive to eruptive activity in November 2005, coinciding with previous estimates of the initiation of dike intrusion Models formulated using all datasets (seismic, gas, and geodetic) distinguish between non‐eruptive and eruptive data better than models trained on a single data type alone